Clinical outcome of posterior dynamic stabilization of lumbar spine: Experience in Indian and African population - Viral B Shah; Prateek S Joshi; Praveen B Saxena (Wolters Kluwer Medknow Publications, 2015)
Context: There is an increased interest in stabilization of lumbar spine without fusion as an alternative to traditional fusion for treatment of degenerative lumbar spine disease. Aim: To analyze short term outcomes of pedicle-based dynamic stabilization system (DSS). Setting and Design: Retrospective study of a consecutive series of 42 patients. Materials and Methods: Between 2009 to 2012, 42 patients underwent DSS with or without decompression on total 214 pedicles for various indications and were followed up for 12 months. Clinical improvement was evaluated with the Visual Analogue Scale (VAS) and Oswestry Disability Index (ODI). Post operative complications were noted and radiographic evaluation for screw positioning and loosening was done. Statistical Analysis: SPSS Version 21.0. Levene's Test for Equality of Variances, Chi square test and students T test. Results: Out of 66 stabilized segments in 42 patients accounting for 214 pedicles instrumented, 23(54.8%), 14(33.3%) and 5(11.9%) had 1, 2 and 3 segments stabilized respectively {L4-5 in 18, 42.86%, L4-5-S1 in 10, 23.81%, L5-S1 in 5, 11.90%, L2-3-4-5 and L3-4-5 in 3, 7.14% and L3-4 in 1, 2.38%}. Dynamic stabilization or an additional decompression procedure was done in 29 and 13 patients respectively. The VAS {7.40 ± 0.79 to 1.64 ± 0.93 (P < 0.05)} and ODI {65.92% ± 8.70% to 12.83% ± 6.73% (P < 0.05)} improved. One patient had wound infection, 2 had aseptic skin necrosis, 1 had DVT, 1 required screw repositioning and 1 required unilateral removal of implant for post-op radicular pain. Two patients had persistent sagittal imbalance. Conclusion: DSS is effective and safe in patients with various degenerative lumbar spine diseases.